1997
DOI: 10.1002/(sici)1098-2264(199708)19:4<267::aid-gcc9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations in primary breast cancers and their metastases: Direct comparison using modified comparative genomic hybridization

Abstract: Breast tumor development and progression are thought to be driven by an accumulation of genetic alterations, but little is known about the specific changes that occur during the metastatic process. We analyzed pairs of primary breast cancers and their matched lymph node metastases from 11 patients, pairs of primaries and distant metastases from three patients, and pairs of primaries, and local recurrences from two patients by using comparative genomic hybridization (CGH). Simultaneous hybridization analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
92
0
3

Year Published

1999
1999
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(105 citation statements)
references
References 19 publications
10
92
0
3
Order By: Relevance
“…A final region of interest is 9q31-33 that showed loss in 16 of 36 (44%) familial ovarian cancer cases. Loss of 9q has been seen in unselected ovarian cancer (Table 2) and harbors a region that is commonly associated with bladder and renal cell carcinoma (Habuchi et al, 1997;Simoneau et al, 1996), although loss of heterozygosity (LOH) of this region has also been linked to metastatic breast cancer (Minobe et al, 1998;Nishizaki et al, 1997). Our analyses suggest that losses at 17p12-13, Xp22, 18q21, 13q14, and 9q31-33 in ovarian cancer are unrelated to hereditary predisposition.…”
Section: Lossesmentioning
confidence: 60%
“…A final region of interest is 9q31-33 that showed loss in 16 of 36 (44%) familial ovarian cancer cases. Loss of 9q has been seen in unselected ovarian cancer (Table 2) and harbors a region that is commonly associated with bladder and renal cell carcinoma (Habuchi et al, 1997;Simoneau et al, 1996), although loss of heterozygosity (LOH) of this region has also been linked to metastatic breast cancer (Minobe et al, 1998;Nishizaki et al, 1997). Our analyses suggest that losses at 17p12-13, Xp22, 18q21, 13q14, and 9q31-33 in ovarian cancer are unrelated to hereditary predisposition.…”
Section: Lossesmentioning
confidence: 60%
“…None of the alterations identified in myoepithelial carcinomas are unique, and they have been previously described in invasive breast carcinomas with luminal phenotype (Buerger et al, 1999;Nishizaki et al, 1997;Roylance et al, 1999;Schwendel et al, 1998;Tirkkonen et al, 1998). The most common alterations identified in myoepithelial carcinoma (loss of 16q and 17p) are also regions commonly deleted in ductal carcinomas of no special type.…”
Section: Discussionmentioning
confidence: 95%
“…The most striking observation from this study is the paucity of alterations identified in myoepithelial carcinomas (mean 2.1) compared with "ordinary" breast carcinomas having luminal differentiation. The mean number of alterations reported in the literature in Grade I invasive ductal carcinomas of no special type is 5.4 (range of means is 3.6 -8.0), and 11.7 in Grade III tumors (range of means 8.4 -13.8) (Buerger et al, 1999;Nishizaki et al, 1997;Roylance et al, 1999;Schwendel et al, 1998;Tirkkonen et al, 1998). The data in myoepithelial tumors are surprising in view of their aggressive morphology and behavior.…”
Section: Discussionmentioning
confidence: 98%
“…The copy number alterations of chromosome 8 detected by comparative genomic hybridization typically consist of gains on the q-arm, either entire 8q or only its telomeric parts (3)(4)(5). These aberrations have commonly been interpreted to reflect amplification of the c-myc oncogene, which is located at 8q24.1.…”
mentioning
confidence: 99%